Penerapan Customer Satisfaction Index (CSI) oleh PT Nusantara TV Sebagai Alat Ukur Layanan Dalam Meningkatkan Loyalitas Pemirsa - Desmon Baginda Silaen (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the implementation of the Customer Satisfaction Index (CSI) by PT Nusantara TV in measuring the quality of broadcast services and its contribution to audience loyalty. This research uses a descriptive quantitative approach with primary data obtained through questionnaires distributed to 200 respondents in Jakarta. The results show that the Customer Satisfaction Index, which consists of customer expectations, performance perception, and overall satisfaction indicators, has a significant positive relationship with audience loyalty. This finding indicates that systematic satisfaction measurement can serve as a strategic tool to maintain and enhance audience loyalty amid digital media competition. This study recommends improving program quality, interactivity, and data-driven approaches to address the needs of young audiences.